2008
DOI: 10.4028/www.scientific.net/msf.575-578.1433
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Scale FEM Simulation of Wire Fracture during Drawing of Perlitic Steel

Abstract: The fracture development during wire drawing operation is an important phenomenon governing the productivity as well as the mechanical properties of the drawn wire. The wire drawing processes was investigated in present paper in two separate levels - using the 2-dimensional rigid-plastic finite element method (macro-level) and modelling the microstructure changes (micro-level) by the Representative Volume Elements (RVEs). To predict fracture initiation the phenomenological theory of fracture is used. The influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, in this case only information regarding grain morphology is obtained see e.g. [9]. Details of such procedure applied to the DP steel can be found in [10].…”
Section: Digital Materials Representationmentioning
confidence: 99%
“…However, in this case only information regarding grain morphology is obtained see e.g. [9]. Details of such procedure applied to the DP steel can be found in [10].…”
Section: Digital Materials Representationmentioning
confidence: 99%
“…Theoretical analysis of the heating of the wire in the high speed multistage drawing process was carried out on software Drawing 2D [12], in which the temperature on the surface and average temperature, on the exit form sizing part of die, has been estimated.…”
Section: The Numerical Analysis Of Wire Drawing Processmentioning
confidence: 99%
“…It was assumed that the surface of the die and wire the conditions of friction Amont-Coulomb. Conditions of contact and friction between the material and the tool was modeled using the method of Kara function [12]. The coefficients of friction µ = 0.02 adopted on the basis of works [1,15].…”
Section: The Numerical Analysis Of Wire Drawing Processmentioning
confidence: 99%
“…Due to the high responsibility of the end-use application of products made from pearlite wire, an urgent issue is the consideration of these microstructure evolution features in the design of processing technologies for such steels. Few papers devoted to multiscale computer simulation of pearlite steels drawing clearly demonstrate the expediency and relevance of studies of micro stresses and micro deformations at the level of pearlitic colonies [12][13][14]. It was observed that the stress-strain state, even at the scale level of individual perlite colonies, is characterized by a high degree of inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%